2013
DOI: 10.1093/icesjms/fss197
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in coastal zoobenthos in the northern Baltic Sea: the role of abiotic environmental factors

Abstract: Rousi, H., Laine, A. O., Peltonen, H., Kangas, P., Andersin, A-B., Rissanen, J., Sandberg-Kilpi, E., and Bonsdorff, E. 2013. Long-term changes in coastal zoobenthos in the northern Baltic Sea: the role of abiotic environmental factors – ICES Journal of Marine Science, 70: 440–451. We investigated site-specific changes in a coastal zoobenthic community during 1964–2007 in the northern Baltic Sea. Multivariate analysis indicated that the community structure had changed. The amphipods Monoporeia affinis and Ponto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 36 publications
4
32
1
Order By: Relevance
“…caused by food supply due to sedimentation of the spring phytoplankton bloom (Cibic et al 2007b) or by oxygen deficiency due to high temperatures in late summer (Reiss & Kröncke, 2005). Although our results do not follow this general pattern dictated by seasonality, they are in accordance with those reported by Clarke & Frid (2001), Warwick et al (2002) and Rousi et al (2013) who also observed major yearly differences http://epublishing.ekt.gr | e-Publisher: EKT | Downloaded at 12/05/2018 10:06:52 | in macrofaunal structure rather than seasonal ones. According to the findings of these authors, macrofaunal development was strictly linked to particular environmental variations, such as changes in grain size, sedimentation rate and high temperature.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…caused by food supply due to sedimentation of the spring phytoplankton bloom (Cibic et al 2007b) or by oxygen deficiency due to high temperatures in late summer (Reiss & Kröncke, 2005). Although our results do not follow this general pattern dictated by seasonality, they are in accordance with those reported by Clarke & Frid (2001), Warwick et al (2002) and Rousi et al (2013) who also observed major yearly differences http://epublishing.ekt.gr | e-Publisher: EKT | Downloaded at 12/05/2018 10:06:52 | in macrofaunal structure rather than seasonal ones. According to the findings of these authors, macrofaunal development was strictly linked to particular environmental variations, such as changes in grain size, sedimentation rate and high temperature.…”
Section: Discussionsupporting
confidence: 84%
“…The taxonomic composition of the macrofaunal community during the study period revealed a typical community of sandy-mud and detrital sediments, as previously reported for the Gulf of Trieste (Mavrič et al, 2010;Faresi et al, 2012), for the northern Adriatic Sea (Simonini et al, 2004;Occhipinti-Ambrogi et al, 2005;Franzo et al, 2015), and worldwide (Warwick et al, 2002;Rousi et al, 2013;Somerfield et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…, Rousi et al . , Jansson et al . ), but the values for these environmental variables in upper Cook Inlet are well within the optimal range for M. balthica (Kube et al .…”
Section: Discussionmentioning
confidence: 99%
“…Environmental characteristics (e.g. salinity, dissolved oxygen, temperature) can strongly affect the growth, shell attributes and survival of M. balthica (Jansen et al 2007a, Rousi et al 2013, Jansson et al 2015, but the values for these environmental variables in upper Cook Inlet are well within the optimal range for M. balthica (Kube et al 2006, Compton et al 2007, Jansen et al 2007b, Rousi et al 2013.…”
Section: Impact Of M Balthica Quality On Rock Sandpiper Winter Ecologymentioning
confidence: 99%
“…Marenzelleria, however, is an introduced species. After its introduction in the early 1990's, it has spread to almost all coastal and sea areas in Finland (Olenin and Leppäkoski, 1999;Paavola et al 2008;Rousi et al, 2013), and its effects on the environment, such as on benthic nutrient fluxes (Hietanen et al, 2007) and as a possible facilitator (Norkko et al, 2012), are currently subject of intense discussion. M. edulis, one of the most common species in the northern Baltic proper, occurred more sporadically in the sampled area with most individuals found on the sampling point with rocky bottom (Ap3).…”
Section: Discussionmentioning
confidence: 99%